2019
DOI: 10.1186/s13613-019-0496-9
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent initiation of intra-aortic balloon pumping with extracorporeal membrane oxygenation reduced in-hospital mortality in postcardiotomy cardiogenic shock

Abstract: BackgroundVeno-arterial extracorporeal membrane oxygenation (VA-ECMO) is widely used in postcardiotomy cardiac shock (PCS). The factors that affect mortality in patients who receive ECMO for PCS remain unclear. In this study, we analyzed the outcomes, predictive factors and complications of ECMO use for PCS.MethodsA total of 152 adult subjects who received VA-ECMO for PCS in Fuwai Hospital were consecutively included. We retrospectively collected the baseline characteristics, outcomes and complications. Baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…As VA‐ECMO increases afterload due to retrograde flow toward the aortic valve, this causes left ventricular distention that can result in pulmonary edema and hemorrhage 47,48 . The use of IABP helps to reduce afterload and improve coronary blood flow 49,50 . Alternatively, Impella use helps to support blood flow and unload the left ventricle; however, it does not improve coronary perfusion 50 .…”
Section: Future Of Ecmo In Cardiac Surgerymentioning
confidence: 99%
“…As VA‐ECMO increases afterload due to retrograde flow toward the aortic valve, this causes left ventricular distention that can result in pulmonary edema and hemorrhage 47,48 . The use of IABP helps to reduce afterload and improve coronary blood flow 49,50 . Alternatively, Impella use helps to support blood flow and unload the left ventricle; however, it does not improve coronary perfusion 50 .…”
Section: Future Of Ecmo In Cardiac Surgerymentioning
confidence: 99%
“…Combined support devices also facilitated cardiac function recovery in post-cardiotomy patients. [27][28][29] These findings underline that, despite apparent benefits from the combination of the two devices, further investigations are warranted to conclusively prove the actual role in cardiogenic shock patients requiring TCS.…”
mentioning
confidence: 91%
“…We enthusiastically read the recently published retrospective study by Chen et al [1] who demonstrated that simultaneous use of intra-aortic balloon pumping (IABP) together with veno-arterial extracorporeal membrane oxygenation (VA-ECMO) in postcardiotomy cardiogenic shock (PCS) patients improved short-term survival and reduced peripheral perfusion complications. In this study, 42 (28%) patients were on concomitant IABP and VA-ECMO [1]. While the study adds substantial value to the current knowledge, the current literature about the concomitant use of VA-ECMO and IABP remains controversial [2].…”
mentioning
confidence: 99%
“…Reduced LV afterload and increased blood flow in the coronary arteries by IABP theoretically promote myocardial recovery and could potentially improve survival (although improved survival was never shown) [2, 3]. In the baseline characteristics of patients before VA-ECMO implantation among the non-survivors, they were significantly more hypertension (35 vs. 15%; P < .004), secondary thoracotomies (39 vs. 19%; P < .007), cardiac arrests (34 vs. 11%; P < .001), bedside implantations 42 vs. 11%; P < .0001) and significantly less concomitant insertions of VA-ECMO and IABP (22 vs. 41%; P < .025) when compared with the study survivors [1]. All mentioned variables are well-described risk factors for increased mortality [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation